Enhancing Learning Outcomes in Elementary School Islamic Religious Education through Problem-Based Learning in Zakat Materials - Munif Afifuddin; Mohammad Zuhri (Research Journal on Teacher Professional Development, 2026)
This study aims to determine the improvement in the learning outcomes of fifth-grade students of Srondol Wetan 06 Semarang State Elementary School on zakat material in Islamic Religious Education learning through the application of the Problem Based Learning (PBL) method, and to describe the increase in student activity and cooperation in the learning process. This study uses the Classroom Action Research (CAR) method which is implemented in three cycles, with the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 23 fifth-grade students of Srondol Wetan 06 Semarang State Elementary School. Research data were collected through observation, learning outcome tests, documentation, and field notes. The data analysis technique used is quantitative descriptive analysis to determine the improvement in student learning outcomes and qualitative descriptive analysis to describe the increase in student activity and cooperation during the learning process. The results of the study show that before the action was carried out, the average student learning outcomes only reached 73.7 with a completion rate of 40%, still below the KKTP of 80. After the application of the Problem Based Learning method on zakat material, student learning outcomes increased in each cycle. In Cycle II, the average grade increased to 82.1, with a completion rate of 78%. In Cycle III, almost all students achieved a minimum grade point average (KKTP) of 80, with significant improvements in active participation, group discussions, cooperation, and understanding of the material "Living Spaciously by Sharing." The findings of this study indicate that the Problem-Based Learning method is effective in improving learning outcomes while developing students' collaborative skills in Islamic Religious Education (ISE) in elementary schools. Keywords: Learning Outcomes, Elementary School, Islamic Religious Education, Problem-Based Learning